2012
DOI: 10.1111/j.1600-0447.2012.01896.x
|View full text |Cite
|
Sign up to set email alerts
|

Insular dysfunction and descending pain inhibition in anorexia nervosa

Abstract: We suggest that reduced activity in the left posterior insula might contribute to increased pain thresholds in patients, while increased activations in the right anterior insula and pons mirror augmented sympathetic modulation putatively related to amplification of adrenergic descending pain inhibition. In addition, pain thresholds and brain activations were influenced by disease-inherent depressed mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 62 publications
0
36
0
1
Order By: Relevance
“…39,50 Interestingly, studies using heat pain in patients with anorexia nervosa consis tently found decreased posterior insula responses during stimulation. 51,52 According to Craig, 50 afferent representations of the physiologic condition of the body ascend via the lam ina I spino-thalamo-cortical pathway to the posterior and mid insula. Therefore, reduced posterior insular responses to pain in patients with anorexia nervosa are well in line with the current network analysis measures and might help to ex plain the relative insensitivity to pain, which is typical for this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…39,50 Interestingly, studies using heat pain in patients with anorexia nervosa consis tently found decreased posterior insula responses during stimulation. 51,52 According to Craig, 50 afferent representations of the physiologic condition of the body ascend via the lam ina I spino-thalamo-cortical pathway to the posterior and mid insula. Therefore, reduced posterior insular responses to pain in patients with anorexia nervosa are well in line with the current network analysis measures and might help to ex plain the relative insensitivity to pain, which is typical for this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the anterior insula has been associated with that function, including risk prediction, 37 but the posterior insula tracks changes of interoceptive states and somatosensory processes. 38 This is of interest and importance for anorexia nervosa research because of the disorder's (ill or recovered) association with distorted body perception that has been linked to the insula among other brain regions, 39,40 reduced pain perception that has been linked to the posterior insula, 41,42 reduced interoception measured by heart rate detection tasks, 43 and the altered drive to eat. Thus, altered activation in the posterior insula could be a potentially important marker for altered pathophysiology in individuals recovered from anorexia nervosa; however, this needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for data preprocessing was comparable to that used in our previous studies 17,31 and is described in detail in the Appendix. We focused our statistical analysis on the comparison contrasting the painful thermal stimulation at 45°C with the nonpainful 37°C condition.…”
Section: Functional Data Analysismentioning
confidence: 99%
“…54 A recent study suggested that increased sympathetic modulation might play an important role in pain inhibition in individuals with the disease. 17 Because the PCC is known to be part of the central autonomic network and is mainly involved in parasympathetic modulation, 55 a decreased inhibition of sympathetic modulation could be assumed, leading to increased pain thresholds. Altered pain thresholds might also lead to differences in activation in the PCC area during pain perception.…”
Section: Stgmentioning
confidence: 99%
See 1 more Smart Citation